The Effect of Company Reputation and Customer Relationship Marketing Towards Telkomsel Customer Loyalty in Salatiga City - Abdi , Antonius Surjo; Kusuma, Linda; Ariadi, Gede (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
This research aimed to investigate the effect of company reputation and customer relationship marketing towards Telkomsel customer loyalty in Salatiga City. This study used word-of-mouth marketing variables and structural equation modelling (SEM) as an analysis to test 5 hypotheses. This research was followed by 160 respondents who were users of Telkomsel cellphone card in Salatiga City. This research showed that company reputation and customer relationship marketing significantly affected customer loyalty using Telkomsel cellphone card in Salatiga city. Company reputation significantly affect the word of mouth, but word of mouth did not significantly affect towards customer relationship marketing and customer royalty. Therefore, word of mouth could not mediate company reputation and customer relationship marketing towards Telkomsel customer loyalty in Salatiga city. Further research must examine other cellphone card users to provide new results because the results of this study cannot be representative of all cellphone card operators.